(untitled) (International Journal of Banking and Finance, 2013)
This paper is about the six different SukuÌ„k securities, which originated in 1990s, and are now traded in some 11 markets as the new debt-like securities classed under Islamic finance. The outstanding value of these contracts is estimated to be US 850 billion. This paper proposes a classification for SukuÌ„k contracts as pure debt, equity-based, and asset-backed based on the intrinsic nature and purpose of fund-raising. This classification has more practical use compared to existing classification. Futher, the contract peculiarities of the six instruments (mudaÌ„rabah, mushaÌ„rakah, muraÌ„bahah, ijaÌ„rah, salam and istisnaÌ„h) are carefully specified for the first time. To start a discussion on how the economic behaviour may be modeled for theory building, the potential cash flow pattern of each type of SukuÌ„k contracts is specified. The paper aims to contribute to advanced studies by specifying the basic behavioural characteristics.